2016
DOI: 10.1530/rep-16-0069
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage responses in mammalian oocytes

Abstract: DNA damage acquired during meiosis can lead to infertility and miscarriage. Hence, it should be important for an oocyte to be able to detect and respond to such events in order to make a healthy egg. Here, the strategies taken by oocytes during their stages of growth to respond to DNA damaging events are reviewed. In particular, recent evidence of a novel pathway in fully grown oocytes helps prevent the formation of mature eggs with DNA damage. It has been found that fully grown germinal vesicle stage oocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 75 publications
0
46
0
Order By: Relevance
“…Despite the fact that we can explain the increase of aneuploidy coincidently with maternal age by deterioration of cohesion between sister chromatids [Chiang et al, 2010;Lister et al, 2010] due to the absence of turnover of the cohesin complex during a prolonged prophase arrest [Revenkova et al, 2010;Tachibana-Konwalski et al, 2010], we are still uncertain why the aneuploidy is so high even in oocytes from young individuals in comparison to meiosis in yeast and Drosophila [Hassold and Hunt, 2001]. One of the mechanism, which likely contributes to this higher aneuploidy rate, is the spindle assembly checkpoint (SAC) and specifically changes to its function in oocytes compared to somatic cells [Mailhes, 2008;Jones and Lane, 2013;Touati and Wassmann, 2015;Collins and Jones, 2016].In a previous study, we demonstrated that the SAC in oocytes is unable to detect extensive chromosome alignment and congression defects by using animals generated by crossbreeding of 2 different mouse species, Mus mus- …”
mentioning
confidence: 99%
“…Despite the fact that we can explain the increase of aneuploidy coincidently with maternal age by deterioration of cohesion between sister chromatids [Chiang et al, 2010;Lister et al, 2010] due to the absence of turnover of the cohesin complex during a prolonged prophase arrest [Revenkova et al, 2010;Tachibana-Konwalski et al, 2010], we are still uncertain why the aneuploidy is so high even in oocytes from young individuals in comparison to meiosis in yeast and Drosophila [Hassold and Hunt, 2001]. One of the mechanism, which likely contributes to this higher aneuploidy rate, is the spindle assembly checkpoint (SAC) and specifically changes to its function in oocytes compared to somatic cells [Mailhes, 2008;Jones and Lane, 2013;Touati and Wassmann, 2015;Collins and Jones, 2016].In a previous study, we demonstrated that the SAC in oocytes is unable to detect extensive chromosome alignment and congression defects by using animals generated by crossbreeding of 2 different mouse species, Mus mus- …”
mentioning
confidence: 99%
“…The checkpoint that controls completion of oocyte maturation is the Spindle Assembly Checkpoint (SAC), named after its ability to prevent progression through the cell cycle until the spindle fully formed and chromosomes attached correctly in preparation for anaphase. We and others have recently shown an additional function of this checkpoint, unique to oocytes: its ability to prevent maturation in response to DNA damage10111213. As yet it is untested whether the extent of DNA damage required to activate the SAC-DDR checkpoint can occur pathologically or even physiologically.…”
mentioning
confidence: 99%
“…Recently, however, it was shown that DNA damage, which does not typically activate SAC in other cell types, apparently does so in mouse oocytes, suggesting the checkpoint has been adapted in female germ-cells to prevent DNA damage rather than aneuploidy (Collins and Jones, 2016). Our main finding here is that the same principle does not appear to apply in human oocytes.…”
Section: Discussionmentioning
confidence: 58%
“…In mouse oocytes the SAC can be activated and polar body extrusion prevented by two types of specific intervention; either by DNA damaging agents (Collins and Jones, 2016), or by extreme spindle disruption (Collins and Jones, 2016;Duncan et al, 2009). Our data demonstrates that DNA damage does not robustly activate SAC.…”
Section: Pharmacological Spindle Disruption Prevents Polar Body Extrumentioning
confidence: 75%
See 1 more Smart Citation